Forestry Education in the United States. - Carol C. Green (Issues in Science and Technology Librarianship)
The definition of "forestry" has been debated from the beginning of forestry programs and agencies in the United States in the late 19th century. Forestry has grown into an interdisciplinary subject incorporating many scientific disciplines: soils, wildlife, civil engineering, economics, ecology, agriculture, environmental science, and recreation as well as silviculture and utilization of timber products. U. S. schools and colleges have adjusted their forest-related curricula and organizational structures to accommodate these differences and train their students to succeed within this expanded discipline. Examination of six long-established academic forestry programs illustrates the expansion in the definition of forestry. Program names have changed and in some cases no longer include the word "forestry." However, these program changes are rarely recognized by the general public. At the same time, many forestry collections that support these programs are hidden within larger collections. Subject-specific forestry branch libraries developed in the latter half of the 20th century are being consolidated into larger units and losing their unique identity. The hidden nature of both forestry programs and forestry collections requires continuing efforts to make them visible to both primary users and the general public, and establish their importance in addressing natural resource and environmental issues. [ABSTRACT FROM AUTHOR]